Being and being a teacher in early childhood education: moving meanings (Research, Society and Development, 2020)
The present article aims to expose a reflection on being and being a teacher in Early Childhood Education in relation to the organization of teaching and learning for this segment. It is a research with a qualitative approach, based on the perspective of Historical-Cultural Theory (THC), in which the researches were used: bibliographic, documentary and field. The bibliographic research took as a reference authors such as: Vigotski, Elkonin, Leontiev, Davídov, the documentary research referred to the official guiding framework of Early Childhood Education and the field research was developed through interviews of teachers who work at this level of education. As a tool for data collection, a record form containing information from the documents and the selected bibliography and semi-structured interview were used. Teachers who work in municipal schools of Early Childhood Education, located in the rural area of São José do Mipibu-RN, were interviewed. Considering the need to apprehend the meanings attributed by the subjects participating in the research in relation to the object of study, the data obtained in the interviews were analyzed in line with the methodological proposal of the meaning cores, coined by Aguiar and Ozella (2006), in accordance with the objective analytical method of Vigotski (1984). At the conclusion of the research, we present contributions to the improvement of the organization of teaching-learning in Early Childhood Education, allowing teachers to reflect on the relationships between the organization of teaching-learning processes and the development of children's higher psychic functions.